2002
DOI: 10.1007/s00775-002-0343-5
|View full text |Cite
|
Sign up to set email alerts
|

Hard X-ray microprobe studies of chromium(VI)-treated V79 Chinese hamster lung cells: intracellular mapping of the biotransformation products of a chromium carcinogen

Abstract: The uptake of carcinogenic and mutagenic Cr compounds and the intracellular distribution of their biotransformation products in V79 Chinese hamster lung cells were studied by synchrotron-radiation-induced X-ray emission (SRIXE). SRIXE analysis was performed on whole cells that had been treated with either Cr(III) or Cr(V) 1,10-phenanthroline complexes, or Cr(VI). The high spatial resolution (0.3 microm) and elemental sensitivity (~10(-15) g Cr/cell) of the technique provided detailed maps of Cr and other cellu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
48
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 56 publications
(48 citation statements)
references
References 33 publications
0
48
0
Order By: Relevance
“…10 In addition, SR-XRF is capable of elemental distribution mapping within individual cells at a resolution of 0.2-0.3 µm and has successfully been used to study the uptake of metals in mammalian cells. [12][13][14][15] Studies by Twinning and coauthors 16,17 and Diaz 18 also showed that microprobe SR-XRF was useful in determining the elemental composition and distribution of elements (Si, P, S, K, Ca, Mn, Fe, Co, Ni, Cu and Zn) in a range of marine microalgae isolated from oceanic waters and in two freshwater algae in laboratory culture media, respectively. This study uses correlative microprobe SR-XRF and XANES to investigate the internalisation of Cu in Cu-exposed marine microalgal cells to determine the toxicological modes of action of the metal.…”
Section: Introductionmentioning
confidence: 99%
“…10 In addition, SR-XRF is capable of elemental distribution mapping within individual cells at a resolution of 0.2-0.3 µm and has successfully been used to study the uptake of metals in mammalian cells. [12][13][14][15] Studies by Twinning and coauthors 16,17 and Diaz 18 also showed that microprobe SR-XRF was useful in determining the elemental composition and distribution of elements (Si, P, S, K, Ca, Mn, Fe, Co, Ni, Cu and Zn) in a range of marine microalgae isolated from oceanic waters and in two freshwater algae in laboratory culture media, respectively. This study uses correlative microprobe SR-XRF and XANES to investigate the internalisation of Cu in Cu-exposed marine microalgal cells to determine the toxicological modes of action of the metal.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the Cr was reduced to the impermeable Cr(III) form. Micro-SRIXE images of thin-sectioned cells ( Figure 5) showed the intracellular Cr distribution following Cr(VI) exposure [6]. Cr was localised in two distinct regions.…”
Section: Resultsmentioning
confidence: 99%
“…Na 2 Cr 2 O 7 (Merck, AR grade) was used as received. cis-[Cr(phen) 2 (OH 2 ) 2 ](NO 3 ) 3 .2.5H 2 O was prepared, purified and oxidized to produce the Cr(V) analogue as reported in the literature [4][5][6].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations